A Case Study of Integrating Non-formal Learning for Developing Teaching Resources for Sustainability During a Science Teacher Education Course - Nida, Safwatun; Aksela, Maija (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
This study explores an innovative approach to preparing preservice science teachers at the Science Education Department of Universitas Negeri Malang by engaging them in the development of science teaching resources for sustainability based on the field trip to non-formal partners. These partners include museums, non-governmental organizations (NGOs), and enterprises, providing real-world contexts and authentic learning experiences. The study was participated by 34 student teachers of Science Education of Universitas Negeri Malang. The study employs a qualitative approach, gathering data through students learning artefacts analysis to examine the relevant pedagogical models the students designed during the development of teaching resources for sustainability for school science curriculum. In addition to that, the student teachers’ view on the experience during the course was analyzed according to the questionnaire. Student teachers design various pedagogical models which aimed to equip the students with the awareness on certain components of ecosystem, such as their role to maintain the ecosystem balance, and the ability to address the environmental issues as the effect of human being activities to the ecosystem. Most of the student teachers gave encouraging feedback on the course, both according to the Likert-type questionnaire and the open-ended ones.